1990
DOI: 10.1056/nejm199010253231704
|View full text |Cite
|
Sign up to set email alerts
|

A Prospective Study of the Development of Diabetes in Relatives of Patients with Insulin-Dependent Diabetes

Abstract: Nondiabetic relatives of probands with IDDM who are in the first two decades of life, are members of multiplex pedigrees, and have increased titers of islet-cell antibodies are the most likely to contract IDDM themselves.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
183
1
11

Year Published

1991
1991
2005
2005

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 283 publications
(208 citation statements)
references
References 30 publications
12
183
1
11
Order By: Relevance
“…Individuals with not only high titre ICA but also IAA and/or a decrease in first-phase insulin response have been reported to be at higher risk for Type 1 diabetes [14,45,46]. A large study on ICA in first-degree relatives showed that ICA-positive relatives in multiplex families are at a higher risk for developing Type 1 diabetes than relatives of simplex families [47]. Our finding that 64K antibodies correlate with progressively impaired Beta-cell function and high risk for Type 1 diabetes suggests that 64K antibodies may be a more specific marker 731 for autoimmune processes leading to Type 1 diabetes than ICA and/or IAA.…”
Section: Resultsmentioning
confidence: 99%
“…Individuals with not only high titre ICA but also IAA and/or a decrease in first-phase insulin response have been reported to be at higher risk for Type 1 diabetes [14,45,46]. A large study on ICA in first-degree relatives showed that ICA-positive relatives in multiplex families are at a higher risk for developing Type 1 diabetes than relatives of simplex families [47]. Our finding that 64K antibodies correlate with progressively impaired Beta-cell function and high risk for Type 1 diabetes suggests that 64K antibodies may be a more specific marker 731 for autoimmune processes leading to Type 1 diabetes than ICA and/or IAA.…”
Section: Resultsmentioning
confidence: 99%
“…Such non-genetic factors may either initiate autoimmunity or accelerate/ precipitate beta cell destruction [7]. Follow-up studies of first-degree relatives of type-1 diabetic patients have shown that autoimmunity often precedes clinical disease by many years [8][9][10]. Not all individuals that carry autoantibodies towards the beta cells ultimately develop clinical diabetes, and the signs of autoimmunity may disappear [11][12][13].…”
Section: Introductionmentioning
confidence: 99%
“…In 719 such individuals in the Bart's-Windsor/Bart's-Oxford Study, 2 of 679 ICA negative subjects have developed Type 1 diabetes compared with 16 of 40 ICA positive subjects [9]. Data from Gainesville agree -with 70% of people with ICA levels in excess of 20 JDF units developing Type 1 diabetes, 35% within 5 years of detection [10]. A few false positives may account for the 10-30% of ICA positive subjects who do not progress to Type 1 diabetes.…”
Section: $62mentioning
confidence: 86%